TAQNIN HUKUM KELUARGA ISLAM DI INDONESIA: ANTARA FIKIH KLASIK DAN LEGISLASI MODERN - Alexsander Bahar; Ariangga Ramadhansyah; Fabiel Ahmad (STAI Ali bin Abi Thalib Surabaya, 2026)
This study critically examines the codification (taqnīn) of Islamic family law in Indonesia, focusing on how classical fiqh principles are reconstructed within modern state legislation. The research aims to analyze the historical trajectory of codification, evaluate its substantive framework, and assess the methodological strategies employed — takhayyur, talfīq, siyāsah sharʿiyyah, and textual reinterpretation. Using a normative-legal approach with historical orientation, the study draws on statutory instruments, classical fiqh sources, and selected jurisprudence to identify patterns of negotiation between tradition and modernity.The findings reveal that codification in Indonesia is not a mere transcription of fiqh but a dynamic, state-driven process shaped by historical constraints, judicial practice, and constitutional politics. The Compilation of Islamic Law (KHI) of 1991 exemplifies this negotiation, functioning as a standardized reference that integrates diverse fiqh opinions while ensuring legal certainty. Compared to other Muslim-majority countries — such as Egypt, Pakistan, and Tunisia — Indonesia adopts a compromise model that preserves doctrinal legitimacy while adapting to pluralist and constitutional imperatives.This study contributes to scholarly discourse by positioning taqnīn as a methodological framework for state-driven ijtihād in plural societies. It offers practical implications for judges, who benefit from greater consistency in rulings, and for legislators, who must periodically reform codification to address contemporary challenges such as gender equality and child protection. The novelty of this research lies in its critical evaluation of codification strategies as instruments of legal reform, demonstrating how Indonesia’s model bridges continuity of fiqh tradition with the evolving demands of modern statehood.